Tiger cowrie Cypraea tigris feeds on coral-competing sponge Rhabdastrella globostellata in an Acropora dominated reef of Gulf of Mannar, India. Issue 2 (4th March 2019) - Raj, K. Diraviya; Mathews, G.; Kumar, P. Dinesh
ABSTRACT: Gulf of Mannar (GoM) in the southeast coast of India is known for its coral reefs and reef-associated biodiversity. Corals in GoM were affected to a significant extent by climate change-driven coral bleaching in 2016, and are currently recovering. After the bleaching mortality that corals suffered, the competition for space between corals and sponges is obvious in GoM. Rhabdastrella globostellata is a common marine sponge found overgrowing live coral colonies of the patch reefs in GoM at Pattinamaruthoor in March 2019. Underwater assessment of the reef revealed that 60.06% live coral cover was dominated by Acropora corals (81.91%). Among the acroporans 8.23% of colonies were found overgrown by R. globostellata . During the night dives the tiger cowrie Cypraea tigris was observed to feed on R. globostellata . From this observation the present study infers that C. tigris helps the corals fight these sponges, and concludes that tiger cowries should be protected and promoted to tackle climate change implications.